4×2+6=17

Subtract 6 from both sides of the equation.

4×2=17-6

Subtract 6 from 17.

4×2=11

4×2=11

Divide each term in 4×2=11 by 4.

4×24=114

Cancel the common factor of 4.

Cancel the common factor.

4×24=114

Divide x2 by 1.

x2=114

x2=114

x2=114

Take the square root of both sides of the equation to eliminate the exponent on the left side.

x=±114

Simplify the right side of the equation.

Rewrite 114 as 114.

x=±114

Simplify the denominator.

Rewrite 4 as 22.

x=±1122

Pull terms out from under the radical, assuming positive real numbers.

x=±112

x=±112

x=±112

The complete solution is the result of both the positive and negative portions of the solution.

First, use the positive value of the ± to find the first solution.

x=112

Next, use the negative value of the ± to find the second solution.

x=-112

The complete solution is the result of both the positive and negative portions of the solution.

x=112,-112

x=112,-112

x=112,-112

The result can be shown in multiple forms.

Exact Form:

x=112,-112

Decimal Form:

x=1.65831239…,-1.65831239…

Solve Using the Square Root Property 4x^2+6=17